2015
DOI: 10.1161/jaha.115.002012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Angiography Detection of Abnormal Carotid Artery Plaque in Patients With Cryptogenic Stroke

Abstract: BackgroundMagnetic resonance imaging of carotid plaque can aid in stroke risk stratification in patients with carotid stenosis. However, the prevalence of complicated carotid plaque in patients with cryptogenic stroke is uncertain, especially as assessed by plaque imaging techniques routinely included in acute stroke magnetic resonance imaging protocols. We assessed whether the magnetic resonance angiography–defined presence of intraplaque high-intensity signal (IHIS), a marker of intraplaque hemorrhage, is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 26 publications
4
64
1
2
Order By: Relevance
“…(2) Although case reports and case series have raised the hypothesis that nonstenosing plaque of the cervical and intracranial arteries may cause downstream artery-to-artery embolism, these analyses lacked the control groups needed to support a causal relationship. (1317) We and others found a higher burden of vulnerable atherosclerotic plaque in the cervical ICA upstream of cryptogenic cerebral infarctions as compared to the unaffected ICA,(4,5) which more directly supports the hypothesis that some cryptogenic strokes may arise from unrecognized nonstenosing plaques. On the other hand, a recent analysis from a large population-based study argued against occult atherosclerotic disease as a cause of cryptogenic stroke.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…(2) Although case reports and case series have raised the hypothesis that nonstenosing plaque of the cervical and intracranial arteries may cause downstream artery-to-artery embolism, these analyses lacked the control groups needed to support a causal relationship. (1317) We and others found a higher burden of vulnerable atherosclerotic plaque in the cervical ICA upstream of cryptogenic cerebral infarctions as compared to the unaffected ICA,(4,5) which more directly supports the hypothesis that some cryptogenic strokes may arise from unrecognized nonstenosing plaques. On the other hand, a recent analysis from a large population-based study argued against occult atherosclerotic disease as a cause of cryptogenic stroke.…”
Section: Discussionsupporting
confidence: 83%
“…(3) However, recent studies suggest that artery-to-artery embolism can occur from vulnerable plaque elements in the extracranial internal carotid artery (ICA) even in the absence of significant luminal narrowing. (4,5) It is unknown whether nonstenosing atherosclerotic lesions in the intracranial ICA are also associated with stroke.…”
mentioning
confidence: 99%
“…It is possible that a more directly applicable use of the results of our study may allow clinicians to improve their confidence in identifying a culprit lesion after a stroke of uncertain etiology has occurred so that optimal secondary stroke prevention measures can be initiated. 36,37 Second, we found that the time interval between the onset of ischemic symptoms and CTA for the evaluation of plaque features was relatively inconsistent among included studies. Third, many studies did not include precise descriptions of how causation of ischemic stroke was attributed to a given ICA.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial plaque morphology including intra-plaque hemorrhage [48,49] and increased lipid rich necrotic core volume [50] have also been established as stroke risk factors. In addition, carotid artery studies have demonstrated that complex plaque morphology including intra-plaque hemorrhage, thrombus or fibrous cap rupture is located predominantly on the ipsilateral side of stroke [51][52][53].…”
Section: Clinical Applications 4dflow Mri Of Intracranial Atherosclermentioning
confidence: 99%